Fish Erythrocyte Extracellular Traps (FEETs) are an evolutionarily conserved cellular process triggered by different stimuli. Issue 136 (May 2023) - Rinaldi, Giulia; de Haro, Neila Álvarez; Fernando, Anuruddika J.; Desbois, Andrew P.; Robb, Calum T.; Rossi, Adriano G.
Abstract: Fish erythrocytes remain nucleated, unlike mammalian erythrocytes that undergo enucleation during maturation. Besides oxygen transport, fish erythrocytes are capable of several immune defence processes and thus these cells are candidates for carrying out ETotic responses. ETosis is an evolutionarily conserved innate immune defence process found in both vertebrates and invertebrates, which involves the extrusion of DNA studded with antimicrobial effector proteins into the extracellular space that traps and kills microorganisms. In this present report, we demonstrate that erythrocytes from Danio rerio (zebrafish) produce ETotic-like responses when exposed to both chemical and physiological inducers of ETosis. Furthermore, erythrocytes from Salmo salar (Atlantic salmon) behaved in a similar way. We have termed these ET-like formations, as Fish Erythrocyte Extracellular Traps (FEETs). Several inducers of mammalian ETosis, such as the protein kinase C (PKC) activator phorbol 12‐myristate 13‐acetate (PMA) and the calcium ionophore ionomycin, induced FEETs. Moreover, we found that FEETs depend on the activation of PKC and generation of mitochondrial reactive oxygen species (mROS). This present report is the first demonstration that fish erythrocytes can exhibit ETotic-like responses, unveiling a previously unknown function, which sheds new light on the innate immune arsenal of these cells. Highlights: Fish Erythrocytes Extracellular Traps (FEETs) are released upon physiological and non-physiological stimulation. FEETs represent a previously unknown erythrocyte immune defence mechanism. FEETs represent the first ever ETotic-like responses exhibited by erythrocytes and shed new light on the evolution of ETosis.